EFEKTIVITAS KONSELING MULTIBUDAYA BERBASIS ART THERAPY DALAM REGULASI EMOSI SISWA SMP - Saputra, Reri; Naqiyah, Najlatun; Khusumadewi, Ari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Multicultural school environments require guidance and counseling services that are responsive to cultural diversity and students’ emotional dynamics. Sekolah Indonesia Jeddah (SIJ), as an Indonesian school abroad, accommodates junior high school students from diverse cultural backgrounds, which may contribute to emotional regulation challenges. This study aims to explore the role of multicultural counseling based on art therapy in supporting changes in students’ emotional regulation at Sekolah Indonesia Jeddah. The study employed a qualitative approach using a case study design. Data were collected through in-depth interviews with students, observations of counseling sessions, documentation of art therapy artifacts, and supporting interviews with guidance counselors and homeroom teachers. The research was conducted through three stages: pre-intervention (needs assessment), intervention in the form of multicultural counseling using art therapy, and post-intervention. Data were analyzed thematically to identify patterns of change in emotional regulation. The findings indicate improvements in emotional awareness, a shift from reactive to reflective emotional responses, the development of more adaptive emotional regulation strategies, more constructive management of social conflicts, and more positive interpretations of multicultural experiences. These findings suggest that integrating art therapy into multicultural counseling serves as an effective expressive and reflective medium for enhancing students’ emotional regulation. This study provides practical implications for the development of inclusive and culturally sensitive guidance and counseling services in multicultural school settings. ABSTRAK Lingkungan sekolah multibudaya menuntut layanan bimbingan dan konseling yang mampu merespons keberagaman latar budaya dan dinamika emosi siswa secara adaptif. Sekolah Indonesia Jeddah (SIJ) sebagai sekolah Indonesia di luar negeri memiliki karakteristik siswa SMP yang heterogen, sehingga berpotensi memunculkan permasalahan regulasi emosi. Penelitian ini bertujuan untuk memaknai peran konseling multibudaya berbasis art therapy dalam mendukung perubahan regulasi emosi siswa SMP di Sekolah Indonesia Jeddah. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara mendalam dengan siswa, observasi proses konseling, dokumentasi artefak art therapy, serta wawancara pendukung dengan guru bimbingan dan konseling dan wali kelas. Penelitian dilaksanakan melalui tahapan pra-intervensi (asesmen kebutuhan), intervensi berupa konseling multibudaya berbasis art therapy, dan pasca-intervensi. Analisis data dilakukan secara tematik untuk mengidentifikasi pola perubahan regulasi emosi siswa. Hasil penelitian menunjukkan adanya peningkatan kesadaran emosi, pergeseran respons emosi dari reaktif ke reflektif, berkembangnya strategi regulasi emosi yang lebih adaptif, pengelolaan konflik sosial yang lebih konstruktif, serta pemaknaan yang lebih positif terhadap pengalaman multibudaya. Temuan ini menegaskan bahwa integrasi art therapy dalam konseling multibudaya berfungsi sebagai media ekspresif dan reflektif yang efektif dalam mendukung regulasi emosi siswa. Penelitian ini memberikan implikasi praktis bagi pengembangan layanan bimbingan dan konseling yang inklusif dan sensitif budaya di lingkungan sekolah multikultural.